The Presidential System with a Multiparty System is Based on the 1945 Constitution of the Republic of Indonesia - Nur Afti Aulia; La Ode Husen; Agussalim A. Gadjong (Sovereign: International Journal of Law, 2021)
Coalitions of political parties built within the presidential system, especially in Indonesia, are non-binding and permanent. If government policies or programs are not famous or inline, political parties tend to engage in opposition. This study aims to determine the implementation of the presidential system with a multiparty system and efforts to realize a stable and dynamic government based on the Indonesian constitutional system. This research uses a normative approach. Types and sources of legal materials consist of primary legal materials, secondary legal materials, and tertiary legal materials. The analysis technique used in this research is the hermeneutic analysis method. The study results concluded that with the implementation of the presidential system with a multiparty system, it is rare for a President to be elected and from the majority party. Furthermore, with the election of a minority President and a majority in Parliament, the President will strengthen his position by forming a coalition. However, building a stable coalition is difficult in a multiparty presidential democracy. In this regard, the institutional engineering agenda that needs to be designed includes simplifying the number of factions in Parliament by tightening the threshold requirements for fraction formation; parliamentary coalition regulations aimed at both political blocs (coalition and opposition); strengthening the institution and authority of the Regional Representative Council to balance the House of Representatives so that checks and balances not only occur between the President and the House of Representatives but also between the House of Representatives and the Regional Representative Council.